The examination of impact testing performed on SS-316L specimens fabricated utilizing selective laser melting 3D printer machine - Taib, Mohd Taufik; Abu Zaki, Muhammad Syafiq Syazwan; Rahman, Irfan Ur; Abu Bakar, Mohd Hadzley; Ab Wahab, Norfariza (Institute of Physics, 2024)
The research regarding additive manufacturing methods (AM) is popular among new researchers from industrial workers or university students since this technology is most likely to pioneer manufacturing industries in the future. Almost all the studies conducted by past researchers are related to the material properties of the 3D printing machine regardless of the type of material including Selective Laser Melting (SLM) 3D printing machines which utilize metal powder as the primary material. Plus, there is a study on the difference between virgin and recycled powder material in terms of material properties for SLM 3D printing machines. In this study, we conducted Charpy impact tests on metal specimens fabricated from both virgin and recycled powders, varying the print thicknesses in accordance with ASTM E23 standards. For each thickness parameter, three specimens were produced, irrespective of the material state. The selective laser melting (SLM) machine maintained consistent printing parameters for both virgin and recycled materials, while permitting flexibility in the adjustment of specimen coordinates within the production bed. Therefore, the impact test result will determine which material condition delivers the best result of the specimens’ absorbed energy (J) and impact toughness (J/cm2).